2021
DOI: 10.3390/electronics10192373
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative- and Eco-Driving: Impact on Fuel Consumption for Heavy Trucks on Hills

Abstract: Greenhouse gas emissions are the cause of climate change, which in turn has a negative impact on people and the environment. Reducing the fuel consumption of conventional engines reduces climate-damaging emissions and can, thus, contribute to achieving climate protection goals. In addition, fuel costs are a major cost factor for long-haul trucking. Eco-driving helps to reduce fuel costs when driving on inclines and declines. Due to the high mass and, therefore, high kinetic and potential energy of heavy trucks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…An essential feature of road freight transportation is its substantial fuel consumption. In tasks carried out using trucks, fuel expenditure constitutes between 30 and 41% of the total costs [4]. Conversely, within urban bus transportation [5], fuel expenditures cannot be as much as 75% of the total cost of ownership (TCO).…”
Section: Introductionmentioning
confidence: 99%
“…An essential feature of road freight transportation is its substantial fuel consumption. In tasks carried out using trucks, fuel expenditure constitutes between 30 and 41% of the total costs [4]. Conversely, within urban bus transportation [5], fuel expenditures cannot be as much as 75% of the total cost of ownership (TCO).…”
Section: Introductionmentioning
confidence: 99%
“…High efficiency of operation is the key focus of Smart Industry. It has been shown that the driver’s behavior is a significant factor in fuel efficiency of a vehicle [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. For this reason, in the past decade there has been a surge of studies that try to determine the driving behavior that maximizes fuel efficiency [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%